Integrating Financial, Operational, and Cultural Strategies: A Multidisciplinary Framework for SME Resilience in a Post-Pandemic Tourism Economy - Merta, I Nengah; Mertaningrum, Ni Luh Putu Erma; Puriati , Ni Made (Forum Manajemen, 2025)
This study investigates the multidisciplinary drivers of resilience for small and medium-sized enterprises (SMEs) in Bali, Indonesia, following the COVID-19 pandemic. The global health crisis exposed the vulnerabilities of economies heavily reliant on tourism, revealing significant gaps in understanding how integrated management strategies across finance, operations, human resources, and marketing contribute to sustained recovery. Using a mixed-methods approach, we surveyed 150 SME owners and managers and conducted 15 in-depth interviews to examine their strategic responses to the crisis. Quantitative findings reveal that SMEs employing integrated strategies—combining digital marketing adoption, financial liquidity management, and stakeholder support—demonstrated significantly higher recovery rates. Qualitative insights further highlight the indispensable role of local cultural values, such as Tri Hita Karana, in facilitating community-based adaptation and employee retention. The study makes a novel contribution by proposing a multidisciplinary resilience framework that merges contemporary Western management practices with indigenous Balinese philosophies. This framework offers actionable insights for SMEs, policymakers, and scholars aiming to foster sustainable business recovery in fragile economic ecosystems.   Studi ini menyelidiki pendorong multidisiplin ketahanan bagi usaha kecil dan menengah (UKM) di Bali, Indonesia, setelah pandemi COVID-19. Krisis kesehatan global mengungkap kerentanan ekonomi yang sangat bergantung pada pariwisata, mengungkapkan kesenjangan yang signifikan dalam memahami bagaimana strategi manajemen terpadu di seluruh keuangan, operasi, sumber daya manusia, dan pemasaran berkontribusi pada pemulihan berkelanjutan. Dengan menggunakan pendekatan metode campuran, kami mensurvei 150 pemilik dan manajer UKM dan melakukan 15 wawancara mendalam untuk memeriksa respons strategis mereka terhadap krisis. Temuan kuantitatif mengungkapkan bahwa UKM yang menggunakan strategi terintegrasi—menggabungkan adopsi pemasaran digital, manajemen likuiditas keuangan, dan dukungan pemangku kepentingan—menunjukkan tingkat pemulihan yang jauh lebih tinggi. Wawasan kualitatif lebih lanjut menyoroti peran penting nilai-nilai budaya lokal, seperti Tri Hita Karana, dalam memfasilitasi adaptasi berbasis masyarakat dan retensi karyawan. Studi ini memberikan kontribusi baru dengan mengusulkan kerangka kerja ketahanan multidisiplin yang menggabungkan praktik manajemen Barat kontemporer dengan filosofi adat Bali. Kerangka kerja ini menawarkan wawasan yang dapat ditindaklanjuti bagi UKM, pembuat kebijakan, dan akademisi yang bertujuan untuk mendorong pemulihan bisnis berkelanjutan dalam ekosistem ekonomi yang rapuh.